The Physiological Effect of a Holoparasite Over a Cactus Along an Environmental Gradient - Ossa, Carmen Gloria; Aros-Mualin, Daniela; Mujica, María Isabel; Pérez, Fernanda (Frontiers in Plant Science, 2021)
Echinopsis chiloensis is an endemic cactus from Chile, distributed in a temperature and rainfall gradient between 30° and 35° South latitude, with mean temperatures increasing and precipitation decreasing toward the north. It is the main host of the mistletoe Tristerix aphyllus, a holoparasite completely dependent on the cactus for water, carbon, and minerals. In this study, we investigated the consequences of parasitism over the fitness and physiology of this cactus throughout its distribution range and how it is affected by the environment. We measured five functional traits in eight populations latitudinally distributed, the first three only for the host: reproductive fitness, stomatal traits (density and size), and photosynthesis (during winter and summer); and the last two for the host and parasite: stable isotopes (∂13C and ∂15N), and nutrients (carbon and nitrogen content). The results showed a negative effect of parasitism over fitness of infected cacti. However, the higher nitrogen concentrations in cactus tissues toward the south improved overall fitness. Regarding photosynthesis, we only observed a negative effect of parasitism during the dry season (summer), which is also negatively affected by the increase in summer temperatures and decrease in winter rainfall toward the north. There were no differences in nutrient concentration or in the isotopic signature of healthy and infected cacti. Conversely, we observed a higher carbon and lower nitrogen concentration in mistletoes than in cacti regardless of latitude. The loss of temperature seasonality toward the north increases the C:N ratio, and the values between the parasite and its host diverge. ∂15N was similar between parasites and hosts while ∂13C of the parasite was enriched when compared to its host. Overall, the infection by T. aphyllus affects Echinopsis chiloensis fitness but showed no strong effects over the cactus physiology, except for the summer photosynthesis. Therefore, our data revealed that E. chiloensis response to T. aphyllus infection is sensitive to environmental changes in a way that could be strongly impacted by the desertification projected for this area due to climate change.